Africa Agriculture Transformation Scorecard: performance and lessons. Madagascar - Ndoricimpa, A.; Matchaya, Greenwell C.; Solonitompoarinony, J.; Randrianaivomanana, A. L. (Regional Strategic Analysis and Knowledge Support System for Eastern and Southern Africa, 2023)
The Malabo Declaration on accelerated agricultural growth and transformation for shared prosperity and improved livelihoods is a set of goals that were adopted by Heads of State and Government of the African Union in 2014 in Malabo, Equatorial Guinea (AUC 2014). To translate the seven Malabo commitments into results, a call for action was made by the Heads of State and Governments, by calling upon the AU Commission and the NEPAD Planning and Coordinating Agency, in collaboration with partners, to initiate a review process to be conducted on a biennial basis starting 2017, with an objective of tracking, measuring, and reporting progress towards achieving the Malabo Declaration commitments by 2025. Three Biennial Reviews (BR) have been conducted—the inaugural BR in 2017, the second BR in 2019, and the third and most recent BR in 2021. This brief draws on the report for the third BR to summarize the performance of Madagascar in pursuit of the seven Malabo commitments and assesses the challenges faced and the lessons learned by the country across the three BRs. At the time of the third BR in 2021, Madagascar was not on-track to achieve any Malabo commitment by 2025. This represented a setback from the first and second BRs, which found Madagascar to be on track for achieving three and two commitments, respectively. A key recommendation from the analysis is for the government to increase the proportion of rural women that are economically empowered and successful in agriculture. The country should promote initiatives that facilitate participation by women in gainful and attractive agribusiness opportunities.